Laundry Wastewater Treatment by Hybrid System of Biofilter and Vertical Surface Flow Constructed Wetland with Equisetum hyemale - Violenta, Nadya; Bawole Sutanto, Haryati; Prihatmo, Guruh (Universitas Kristen Duta Wacana, 2022)
Laundry activity or washing clothes is an activity that almost all people in the world do. Like other human activities, laundry activity also produces waste or filth. But, the waste is often directly disposed of any treatment to the water like rivers or lakes. It finally causes contamination to the nature, one of them is known as eutrophication or nutrition enrichment, then it will harm the growth of aquatic organisms. To overcome the problem, the laundry waste needs to be treated before it is disposed of the nature. Biofilter and Constructed Wetland are low cost systems and easily handled, so this system is suitable to be applied on small or household scale. Equisetum hyemale is a decorative plant which has already been used to treat many wastewater, and proves it’s effectiveness in reducing the pollutant in wastewater. In this research a hybrid system of Biofilter with additions of activated carbon and Constructed Wetland with Equisetum hyemale is used to treat laundry wastewater, with HRT of 4 days we found a decrease of tested parameters, TDS 346.94 mg/L (21.15 %); TSS 11.25 mg/L (88.88 %); BOD 31.86 mg/L (63.68 %); Phosphate 3.41 mg/L (83.28 %); and Detergent 1.10 mg/L (93.1 %).